TYPES OF VERBAL PHRASES IN MODERN ENGLISH (American Journal of Interdisciplinary Research and Development, 2023)
This article examines the systematic behavior of the Ìdọ́mà verb and verb phrase It studies the internal structure of the verb. The motivation for this study is due the fact that, there is paucity of research in the syntax, and particularly the verb structure of the language. The analysis is basically done using the descriptive method. The data were elicited from daily utterance of speakers of the language as well as the intuitive knowledge of two of the researchers. The study establishes that Ìdọ́mà verbs are largely monosyllabic in structures: CV, CVCV, CCV and CVV, but the most common is the CV structure.